A simple estimate of gravitational wave memory in binary black hole systems. (5th August 2016) - Garfinkle, David
Abstract: A simple estimate is given of gravitational wave memory for the inspiral and merger of a binary black hole system. Here the memory is proportional to the total energy radiated and has a simple angular dependence. Estimates of this sort might be helpful as a consistency check for numerical relativity memory waveforms.